2012
DOI: 10.4103/2278-9626.105354
|View full text |Cite
|
Sign up to set email alerts
|

Additive and synergistic effect of phytochemicals in prevention of oral cancer

Abstract: Increasing the consumption of fruits, vegetables, and whole grains is a practical strategy to optimize good health and to reduce the risk of various chronic diseases and cancer. There are approximately 5,000 individual phytochemicals which have been identified. These interfere with multiple important cellular pathways and play an important role in maintaining balance between health and disease. This article aims to provide awareness of various additive and synergistic effects of these natural occurring chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…; Chandra et al . ), as opposed to an extracted terpenoid constituent administered in isolation (Druesne‐Pecollo et al . ).…”
Section: Application Of Amf To Improve Plant Terpenoid Accumulation Imentioning
confidence: 99%
See 1 more Smart Citation
“…; Chandra et al . ), as opposed to an extracted terpenoid constituent administered in isolation (Druesne‐Pecollo et al . ).…”
Section: Application Of Amf To Improve Plant Terpenoid Accumulation Imentioning
confidence: 99%
“…In addition, a number of terpenoids are also associated with bioactive properties of potential benefit to human health (Chandra et al . ; Ku & Lin ; Martin et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we observed that LycT yielded lycopene phyto-complex (LycT) which delayed and reduced the severity of NDEA-induced HCC as indicated by histopathology, tumor statistics and antioxidant defence system analysis[ 21 ]. The presence of a myriad number of compounds in the extract has been reported to enhance the medicinal properties of active components through synergistic effects[ 29 , 30 ]. The therapeutic activity of a medicinal plant is not due to a single component or a few components.…”
Section: Discussionmentioning
confidence: 99%
“… 167 , 168 Myriad number of phytochemicals present in fruits, vegetables, herbs etc have been demonstrated to have a wide range of biological activities that are responsible for their medicinal properties. 169 , 170 …”
Section: Growing Prospects Of Botanicalsmentioning
confidence: 99%